Performance of submergence tolerant rice (Oryza sativa) genotypes carrying the Sub1 quantitative trait locus under stressed and non-stressed natural field conditions - Sarkar, R K; Panda, D; Patnaik, S S C; Reddy, J N; Mackill, David J; Ismail, Abdelbagi M (The Indian Journal of Agricultural Sciences, 2011)
The experiment were conducted during rainy season of 2005–07 under favourable rainfed lowlands and controlled submergence at Cuttack, as well as under natural farmers’ field. Under flash-flooding, genotypes with Sub1 survived complete submergence stress with turbid water for up to 12 days, whereas genotypes without Sub1 did not survive. The submergence stress was not so severe in farmers’ fields, yet ‘Swarna’ Sub1 gave higher grain yield than ‘Swarna’ at all sites with a yield advantage of up to 1.65 tonnes/ha (an average of 0.81 tonnes/ha over five sites). The results suggest that rice genotypes with Sub1 have great potential for improving the productivity of rainfed lowland rice prone to flashflooding.